Legal Protection and Efforts to Settle Indemnity Against Bankruptcy Cases - Yudha, Satria Asdi (Riviera Publishing, 2025)
The banking system is one of the sectors related to banks and has a very important function (crucial) in the economic aspects of a country. In implementing operational activities, the Bank applies the precautionary principle to maintain the health of the bank and avoid losses to the interests of customers. The purpose of this study is to analyse the legal protection of bank customers who experience bankruptcy and efforts to settle bank customer claims and the compensation process available in the case of bankruptcy of a bank. This method is normative juridical research, using a statutory approach and conceptual approach, using descriptive analysis techniques. The result of this research is that the Bankruptcy Law provides detailed legal protection for bank customers, including the right of access to information, the right to payment, deposit protection, segregated asset protection, and the right to file claims. The bankruptcy resolution mechanism involves a series of legal steps and procedures aimed at protecting the interests of customers, creditors, and shareholders, as well as maintaining the stability of the financial system. Banks may also take alternative measures before filing for bankruptcy to minimise negative impacts. The decision to file for bankruptcy has significant legal implications, including legal protection, court supervision, and consequences for the board.